Complete Genome Analysis Reveals the Quorum Sensing-Related Spoilage Potential of Pseudomonas fluorescens PF08, a Specific Spoilage Organism of Turbot (Scophthalmus maximus) - Wang, Dangfeng; Cui, Fangchao; Ren, Likun; Tan, Xiqian; Lv, Xinran; Li, Qiuying; Li, Jianrong; Li, Tingting (Frontiers in Microbiology, 2022)
Pseudomonas fluorescens is a common specific spoilage organism (SSO) of aquatic products. The spoilage ability of SSO can be regulated by the quorum sensing (QS) system. However, the QS system in P. fluorescens and their relationship with the spoilage potential have not been systematically analyzed. In the present study, the complete genome of P. fluorescens PF08 isolated from spoilage turbot was sequenced. The identification of key genes that involved in the QS, enzyme synthesis, sulfur, and amino acid metabolism explained the spoilage potential of P. fluorescens PF08. Results of quantitative real-time PCR revealed the key role of the P. fluorescens PF08 QS system in regulating the expression of spoilage-related genes and its sensitivity to environmental stress. These findings provide insight into the spoilage features of P. fluorescens PF08 from a genomic perspective. The knowledge may be valuable in the development of new strategies for the targeted inhibition of aquatic product spoilage based on QS interference.